2016
DOI: 10.1128/microbiolspec.tnmi7-0023-2016
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Tuberculosis

Abstract: The increase in type 2 diabetes mellitus (DM) patients in countries where tuberculosis (TB) is also endemic has led to the reemerging importance of DM as a risk factor for TB. DM causes a 3-fold increase in TB risk and a 2-fold increase in adverse TB treatment outcomes. Given the sheer numbers of DM patients worldwide, there are now more TB patients with TB-DM comorbidity than TB-HIV coinfection. There is an urgent need to implement strategies for TB prevention and control among the millions of DM patients exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
141
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 81 publications
3
141
0
17
Order By: Relevance
“…Spanning back to 1947, a review of diabetes and Mtb co-infection reported that 50% of diabetics succumbed to pulmonary TB (10). In recent years the epidemic has grown, with the number of individuals with Diabetes-TB overtaking those with HIV-TB (14); which can be attributed in part, to the positive impacts that antiretroviral therapy is having on reducing TB-HIV co-infection (15). Moreover, a recent multi-country cohort study found that patients with Diabetes-TB had more severe TB disease compared to individuals without diabetes (16).…”
Section: Introductionmentioning
confidence: 99%
“…Spanning back to 1947, a review of diabetes and Mtb co-infection reported that 50% of diabetics succumbed to pulmonary TB (10). In recent years the epidemic has grown, with the number of individuals with Diabetes-TB overtaking those with HIV-TB (14); which can be attributed in part, to the positive impacts that antiretroviral therapy is having on reducing TB-HIV co-infection (15). Moreover, a recent multi-country cohort study found that patients with Diabetes-TB had more severe TB disease compared to individuals without diabetes (16).…”
Section: Introductionmentioning
confidence: 99%
“…This emphasises the need for studies reporting a thorough characterisation of DM and other host factors with multivariable analysis in order to reach reliable conclusions. [1] The first report of the association between DM and TB was documented by Avicenna (980-1027 AD) over one thousand years ago. Since that time, the relationship between diabetes mellitus (DM) and tuberculosis (TB), and the nature of their interaction with regards to comorbidity are largely suggested by numerous epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia may also compromise Mtb killing by affecting the microvasculature and reducing lung tissue perfusion for optimal immune surveillance. 7 In addition, Arce-Mendoza et al (2008) reported that DM also affects the expression of receptors like CD64, CD206 and RAGE in monocytes. 12 Other possible factors that may impact the host response in patients with DM are short-chain fatty acids (SCFAs).…”
Section: Discussionmentioning
confidence: 99%
“…6 A systematic review of 13 observational studies found that DM increases the risk of TB by three-fold. 7 Thus, patients with DM comorbidity may pose a greater challenge the control of TB. 8…”
mentioning
confidence: 99%